Synthesis New Triethylammonium Salts as Corrosion Inhibitors for Mild Steel in 1 M H2SO4 - S. Muhsin, Mariam; S. Shihab, Mehdi (Al-Nahrain Journal of Science, 2023)
Some new triethylammonium salts, namely triethylammonium 4-(cyclohexyl-amino)-4-oxobut-2-enoate(B1), triethylammonium 5-(cyclohexylamino)-5-oxopentanoate (B2), triethylammonium 4-(cyclohexylamino)-4-oxobutanoate (B3) were synthesized as a corrosion inhibitor for mild steel. These salts could test in one molarity sulfuric acid at room temperature for 24 hours by using weight of losing method. The results revealed that the efficiency of inhibition of all triethylammonium salts were high at the maximum concentration of triethylammonium salt. The increase concentration of inhibitors is associated with decreasing the rate of corrosion, but the increasing of efficiencies of inhibition, and a greater degree of surface covering. Adsorption values of the free energy were used to illustrate the effects of physisorption for (B1, B2, and B3), which was helpful in forecasting the natural interaction between organic corrosion inhibitor molecules and the metal surface of steel.